PENULISAN PARAGRAF DEDUKTIF DALAM BENTUK AKSARA LAMPUNG - Sabila, Amy (JURNAL PESONA, 2018)
AbstractThe objective of the study is to describe writing of deductive paragraphs into Lampung script. This research used qualitative descriptive method including collecting and analysis data. The first step, researcher used written tests and notes as the main data. The data analysis in this research is Padan method. The researcher got the result data. First, inaccuracy the use of the script